2015
DOI: 10.1017/s0021859615000106
|View full text |Cite
|
Sign up to set email alerts
|

Assessing genotype-by-environment interactions and trait associations in forage sorghum using GGE biplot analysis

Abstract: Forage sorghum is an important component of the fodder supply chain in the arid and semi-arid regions of the world because of its high productivity, ability to utilize water efficiently and adaptability to a wide range of climatic conditions. Identification of high-yielding stable genotypes (G) across environments (E) is challenging because of the complex G × E interactions (GEI). In the present study, the performance of 16 forage sorghum genotypes over seven locations across the rainy seasons of 2010 and 2011… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 36 publications
3
27
0
2
Order By: Relevance
“…The environments E5 and E12 and the environments E3 and E7 fall under the latter. The present study indicated a mixture of crossover and non-crossover types of G × E interaction, which has been reported in various studies (Rakshit et al, 2012 ; Naroui et al, 2013 ; Aruna et al, 2015 ). Furthermore, eliminating similar environments from multilocation trials of sorghum will help in the optimal utilization of resources.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The environments E5 and E12 and the environments E3 and E7 fall under the latter. The present study indicated a mixture of crossover and non-crossover types of G × E interaction, which has been reported in various studies (Rakshit et al, 2012 ; Naroui et al, 2013 ; Aruna et al, 2015 ). Furthermore, eliminating similar environments from multilocation trials of sorghum will help in the optimal utilization of resources.…”
Section: Discussionsupporting
confidence: 86%
“…These environments are in complete contrast to the best yielding environments E3, E8, E12, and E13 for high fodder yield. Several authors identified high-yielding genotypes for grain sorghum (Rakshit et al, 2012;Al-Naggar et al, 2018), forage sorghum (Aruna et al, 2015), and sweet sorghum (Rono et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, 33 derivatives from the population breeding program are evaluated in the four testing locations. The differential ranking of genotypes across locations (hereafter referred to as environments) is caused due to a crossover GEI (Mohammadi and Amri, 2013 ), and a significant GEI for yield and grain mold in sorghum has been reported earlier (Rakshit et al, 2012 ; Aruna et al, 2016 ; Diatta et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the potential known genotypes that are good performers for specific traits give insights into a parental line with trait combinations for enhancing yield. The GGE biplot technique was used to understand the stability of genotypes and also to interpret the complexity of GEI in grain sorghum (Rakshit et al, 2012 ), forage sorghum (Aruna et al, 2016 ), and sweet sorghum (Rao et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…This indicates that any of these traits can be used to indirectly select for maturity and virus resistance. The use of GT biplots to describe interrelationships among traits has been reported previously for other crops such as soybean (Yan and Rajcan, 2002), barley (Yan and Tinker, 2005), wheat (Yan and Tinker, 2006) and forage sorghum (Aruna et al, 2016).…”
Section: Associations Between Traitsmentioning
confidence: 89%